LASER BIOPHOTONICS : Fractional laser microablation of skin: increasing the efficiency of transcutaneous delivery of particles. (30th June 2016) - Genina, E A; Dolotov, L E; Bashkatov, A N; Tuchin, V V
Abstract: We study several regimes of fractional laser microablation using a pulsed Er : YAG laser for producing microchannels of different depth and incisions that allow transcutaneous delivery of particles of different size, namely, Al2 O3 (27 μm), ZrO2 (smaller than 5 μm) and TiO2 (smaller than 100 nm). The shock wave regime was used both for enhancing the penetration of particles into the ablation zones and as an independent method of particle delivery into the skin. Based on optical coherence tomography we assessed the coherent depth of particle detection in the skin in 2 hours, 3 days and 10 days after the administration. The maximal localisation depth (up to 450 μm) was obtained for TiO2 nanoparticles in the regime of incisions with enhancement of particle penetration by pulses of a multiple-beam hydrodynamic shock wave. The results of the study can be useful for developing new methods of transcutaneous delivery of micro- and nanocarriers of medicinal preparations.